PERANCANGAN WEBSITE SISTEM INFORMASI KEBUDAYAAN BETAWI - Normah Normah (CAKRAWALA: JURNAL HUMANIORA BINA SARANA INFORMATIKA, 2016)
Globalization for Betawi people is not a something new. and it is not possible can be prevented,that is because the Betawi is an indigenous tribe inhabit Jakarta, namely the capital city ofIndonesia since the reign of Dutch East Indies already has a diversity residents of variousnationalities, coupled with the ever increasing technological advancements in this era ofmodernization, the challenges faced in so large in its preservation. One of the things we can do toassist the government in the effort to preserve Betawi culture is by utilizing advances in technologyitself in this case using the internet as a medium that can be used to promote Betawi culture back tothe society and even the whole world can access this information via the internet.